Integrating complementary food supplements at scale into national nutrition programmes: Insights from India - Menon, Purnima; Khan, Shariqua Yunus; Sankar, Rajan (Emergency Nutrition Network, 2020)
Every year 27 million babies are born in India. At any time, there is a cohort of over 50 million children under two years old. Good nutrition during the first two years helps to build bodies, brains and immunity for every child; yet, survey after survey tells us there is a real crisis in how babies across India are fed, especially around complementary feeding. Indeed, barely a tenth of Indian babies received a minimally adequate diet, even in 2018. Feeding babies well is no small task. Multiple times a day, every day, parents and caregivers must prepare, feed and clean their infants – adding up to an estimated 5,000 feeding moments in the first two years of life. Parents and caregivers need information, time, resources, skills and support to undertake what is a massive caregiving task over these first two years of a child’s life. Public programmes implemented by frontline health workers and medical professionals typically offer parents advice and information, with research finding varying degrees of impact. Indeed, programmes to provide breastfeeding and complementary feeding information and support to families are a common feature of public policy across South Asia. However, few countries in the region also offer families with young children specially formulated complementary food supplements – fortified cereals, cereal-pulse mixes, eggs – to support infant feeding. Evidence suggests that, in food-insecure populations, either food or cash should be provided to families to support infant feeding1. India and Sri Lanka are two of the countries in South Asia that include public provisioning of complementary foods in their nutrition programmes at national scale.